Successful breastfeeding: a global intervention for a physiological process - Corona, M.F; Cataldi, P.; Zaccagnini, G.; Maddaluno, S.; Capone, V.; Conti, A.; Carlucci, D.; Silvano, S.; Bertone, A.; Parmigiani, Stefano (Acta Biomedica Atenei Parmensis, 2016)
In our perinatal unit we applied the ten steps of WHO/UNICEF for Baby Friendly Hospital Initiative and evaluated the percentage of exclusive (EBF) or complementary breastfeeding (CBF), and of formula fed (FF) healthy full-term infants (HFI) at hospital discharge (HD). HFI performing EBF at HD were 85.3%, a quite high value. At the age of 3 mths EBF percentage ranged between 59-62.4%, and at 6 mths it decreased to 51.7-37.7%. Customer satisfaction questionnaire at HD ranked “good” to “very good” in 92.8%. Causes of breastfeeding reduction with time and comparison with previous and actual situation in Italy and civilized countries are discussed.